Analisis Valuasi Saham Pt. Semen Indonesia (Persero) Tbk Dengan Metode Discounted Cash Flow (DCF) - Dina Yeni Martia; Wiwik Setyawati; Yuli Hastuti (Politeknik Negeri Semarang, 2018)
As an investors should be able to consider and conduct an assessment of shares that can provide optimal returns in making investment decisions. Assessment can be done by analyzing the fairness of stock price of the company. This study aims to determine the stock price of PT. Semen Indonesia of the period 2014-2016. The method used in this research is fundamental analysis using Discounted Cash Flow (DCF) approach. The result of this study shows that PT. Semen Indonesia’s stock is in an undervalued condition. Therefore, the right decision for the investor is to buy the stock for investment or not to sell the stock in the hope that in the future the stock price will rise.